PERSPEKTIF KEMARITIMAN DI INDONESIA DAN KAWASAN ASIA TENGGARA LAINNYA - Yuliati Yuliati (Jurnal Sejarah dan Budaya, 2013)
Abstract. Indonesia as a state consisted of islands which wide ranging maritime is larger than land, but in fact Indonesia has became a mainland oriented than the sea. It was implied by scientific traditional who attended into mainland oriented. The sea has not become an important part of Indonesian history if considering Indonesian geohistory position. This essay covers the Musee in Indonesia and Southeast Asia region in which engaging contextual inscription at that time.